Privacy Rights : Moral and Legal Foundations - Moore, Adam D., 1965- (Book collections on Project MUSE., 2010)
"Provides a definition and defense of individual privacy rights. Applies the proposed theory to issues including privacy versus free speech; drug testing; and national security and public accountability"--Provided by publisher